2020
DOI: 10.1021/acs.est.0c02220
|View full text |Cite
|
Sign up to set email alerts
|

Biological Effects of Hydrocarbon Degradation Intermediates: Is the Total Petroleum Hydrocarbon Analytical Method Adequate for Risk Assessment?

Abstract: In crude oil contaminant plumes, the dissolved organic carbon (DOC) is mainly hydrocarbon degradation intermediates only partly quantified by the diesel range total petroleum hydrocarbon (TPHd) method. To understand potential biological effects of degradation intermediates, we tested three fractions of DOC: (1) solid-phase extract (HLB); (2) dichloromethane (DCM-total) extract used in TPHd; and (3) DCM extract with hydrocarbons isolated by silica gel cleanup (DCM-SGC). Bioactivity of extracts from five wells s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…The NVDOC composition in the plume is dependent on the composition of the parent petroleum source and varies with distance due to a continuum of biodegradation progression (Podgorski et al 2021). This metabolite pool is important when assessing potential health risks of these groundwaters (McGuire et al 2018; Bekins et al 2020). McGuire et al (2018) conducted toxicity assays with waters from this site and found a positive relationship between the NVDOC concentration and a subset of molecular targets, pointing to the need for greater understanding of the potential toxicity associated with the transformation products present in hydrocarbon impacted waters.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The NVDOC composition in the plume is dependent on the composition of the parent petroleum source and varies with distance due to a continuum of biodegradation progression (Podgorski et al 2021). This metabolite pool is important when assessing potential health risks of these groundwaters (McGuire et al 2018; Bekins et al 2020). McGuire et al (2018) conducted toxicity assays with waters from this site and found a positive relationship between the NVDOC concentration and a subset of molecular targets, pointing to the need for greater understanding of the potential toxicity associated with the transformation products present in hydrocarbon impacted waters.…”
Section: Resultsmentioning
confidence: 99%
“…Predictions of some of the long‐term effects of these reactions include persistent contamination of groundwater by hydrocarbon partial transformation products, the oxyhydrocarbons (Bekins et al 2016; Podgorski et al 2018; Bekins et al 2020), and arsenic released from aquifer sediments (Ziegler et al 2021). These secondary effects of hydrocarbon degradation have been documented in this and other groundwater plumes containing hydrocarbon source zones (Stasik et al 2015; Geng et al 2017; Smith et al 2019; Schreiber and Cozzarelli 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…OxyPAHs are a class of compounds that are commonly missed in traditional TPH analysis. 120 The reported results expand on traditional TPH methods by identifying two specific oxyPAHs in crude oil and emphasizing the mixture's complexity due to methylated homologues in both fuel types. Although the list of oxyPAHs and PAHs used in this study is not comprehensive of all the compounds in HOPs formed from CI crude oil and diesel, some promising compounds and relationships can be used to track compositional changes of HOPs for a cheaper and more routine analysis.…”
Section: Resultsmentioning
confidence: 82%
“…Sediment-bound organic matter may also play a role in sequestering trace metals. Recent groundwater samples from the Bemidji plume indicated a zone with elevated nonvolatile dissolved organic carbon (NVDOC) concentrations ∼10–15× greater than background levels occurring between 39 and 102 m downgradient from well 421 (the center of the original oil pool), peaking at 67 m downgradient. , This zone roughly corresponds to the transition between methanogenic and Fe-reducing conditions. Within this zone, dissolved organic constituents transition from predominantly reduced aliphatics to predominantly carboxyl-rich alicyclic compounds, particularly benzene polycarboxylic acids .…”
Section: Discussionmentioning
confidence: 99%